Increased cardiovascular risk after pre‐eclampsia in women with dysglycaemia. Issue 1 (13th December 2012) - McDonald, S. D.; Yusuf, S.; Walsh, M. W.; Lonn, E.; Teo, K.; Anand, S. S.; Pogue, J.; Islam, S.; Devereaux, P. J.; Gerstein, H. C.
Abstract Aims Compared with women with uncomplicated pregnancies, women with a history of pre‐eclampsia have two to five times the risk of cardiovascular disease. It is not known whether this risk is related to albuminuria, a known cardiovascular risk factor that is part of the definition of pre‐eclampsia and that often persists after delivery. Our objective was to determine if the high risk of cardiovascular disease in women with pre‐eclampsia is accounted for by known cardiovascular risk factors including albuminuria. Methods We performed a cross‐sectional analysis of 4080 dysglycaemic women enrolled in a large randomized controlled trial who provided an obstetric history and had at least one delivery. Blood pressure, height, weight, waist circumference and hip circumference were measured. An oral glucose tolerance test, lipids, an electrocardiogram and an albumin/creatinine ratio from a first morning urine sample were obtained. Results There were 3613 women with no history of pre‐eclampsia during their pregnancies, 108 with severe pre‐eclampsia and 359 with non‐severe pre‐eclampsia. Women with a history of severe pre‐eclampsia had higher rates of previous cardiovascular disease than women with non‐severe pre‐eclampsia or women without pre‐eclampsia (87, 72 and 72%, P = 0.0019). The high risk of previous cardiovascular disease in women with a history of severe pre‐eclampsia (odds ratio 2.67, 95% CI 1.52–4.70) persisted after adjustment for albuminuria (odds ratio 2.74, 95% CI 1.55–4.83) and also after adjusting for other covariates including albuminuria (odds ratio 3.03, 95% CI 1.69–5.44). Conclusion Even after accounting for cardiovascular risk factors including albuminuria, a history of severe pre‐eclampsia is independently associated with a threefold higher risk of cardiovascular disease.